Evaluation of Therapeutic Effect of Intratrigonal Injection of AbobotulinumtoxinA(Dysport) and Hydrodistention in Refractory Interstitial Cystitis /Bladder Pain Syndrome - Zargham, Mahtab; Mahmoodi, Mahdieh; Mazdak, Hamid; Tadayon, Farhad; Mansori, Mansooreh; Kazemi, Maryam; Khorami, Mohamad Hatef; Saberi, Narjes (Urology Journal, 2020)
Purpose: There are two brands of BotulinumtoxinA(BTXA) that commonly used in treatment of Lower Urinary Tract Disease: OnabotolinumtoxinA(Ona-BTXA) and AbobotulinumtoxinA (Abo-BTXA). The present study was conducted to assess the potential therapeutic and adverse effect of Abo-BTXA or Dysport for IC/BPS. Materials and Methods: Twenty-two out of 52 women diagnosed with IC/BPS who were refractory or had a low response to oral treatments of IC/BPS after 6 months, were included in the study. The end-point was O'Leary-Sant Score (OSS) including “symptoms” and “problem” indexes (ICSI and ICPI respectively) assessment after 1,3and 6 months after Abo-BTXA injection. Each patient underwent cystoscopy and immediately after hydrodistention received intratrigonal injections of 300 IU of Abo-BTXA (Dysport®) in30sites. The effect and side effects of this treatment over time have been investigated. Complications including high post void residual urine (PVR), bladder rupture, and urinary tract infections (UTI) were also assessed. Results: The mean age of patients was 46.2±13.7 years and median OSS was 27.8±5.8.: After single injection ICSI, ICPI and total OSS significantly reduced in 1, 3, and 6 months follow up; rate of decrease total OSS was 39.5%, 36%, 18%, respectively. Its effect lasted up to six months and started to decrease after 1 months (p-value<0.05). Complications included urinary retention (PVR>200ml), bladder rupture, and UTI in 13.5%, 4.3%, and 18% of the patients, respectively. Conclusion: intravesical injection of 300IU Abo-BTX(Dysport) could be a useful approach for the treatment of patients with refractory IC/BPS in a period of six months.